Recombinant Adenoviruses for Delivery of Therapeutics Following Spinal Cord Injury - Sosnovtseva, Anastasiia O.; Stepanova, Olga V.; Stepanenko, Aleksei A.; Voronova, Anastasia D.; Chadin, Andrey V.; Valikhov, Marat P.; Chekhonin, Vladimir P. (Frontiers in Pharmacology, 2022)
The regeneration of nerve tissue after spinal cord injury is a complex and poorly understood process. Medication and surgery are not very effective treatments for patients with spinal cord injuries. Gene therapy is a popular approach for the treatment of such patients. The delivery of therapeutic genes is carried out in a variety of ways, such as direct injection of therapeutic vectors at the site of injury, retrograde delivery of vectors, and ex vivo therapy using various cells. Recombinant adenoviruses are often used as vectors for gene transfer. This review discusses the advantages, limitations and prospects of adenovectors in spinal cord injury therapy.